Tuberculosis in Canada: Detection, Intervention and Compliance - Katya Richardson; Beate Sander; Hongbin Guo; Amy Greer; Jane Heffernan (AIMS Press, 2014)
This paper provides an overview of the current state of TB in Canada by referencing information presented at the workshop, "Tuberculosis: Detection, Prevention, and Compliance." The workshop took place on November 14 and 15, 2012 in Ottawa. The workshop was organized by the Centre for Disease Modeling and the Public Health Agency of Canada as a two-day knowledge translation event that was comprised of scientific and policy focused presentations designed to address four key objectives: (1) Evaluate the success of current tuberculosis (TB) health policies and control strategies in Canada and for specific Canadian sub-populations; (2) Determine the impact of detection, intervention, compliance, and education strategies in terms of TB incidence and prevalence; (3) Develop targets for future interventions by identifying key characteristics of TB epidemics that impact the success of TB health policies and control strategies; (4) Leverage our existing ties with public health decision makers, aboriginal health organizations, and organizations serving the homeless to develop a research community that is based on close collaboration, and will foster national TB control efforts. The workshop elicited robust discussions between experts from a variety of academic disciplines and government officials. A summary of the information presented, comments shared, and questions posed, will provide a comprehensive understanding of the status of TB in Canada and future directions to be taken for improved control of the disease.